Does trade openness cause economic growth in Bangladesh? - Khanom, Sharmina (IIUC Studies, 2020)
Bangladesh has followed a restrictive trade policy immediately after its liberation. But the system was proven wrong, and gradually it opened up its market to others and started to improve its foreign trade. This paper investigates the impact of trade openness on Bangladesh's economic growth using annual time-series data for the period from 1972-73 to 2015-16. The paper uses such econometric tools as unit root test, cointegration test and error correction model to investigate the relationship between the variables. This study revealed a positive association between export and GDP but the opposite relation between import and GDP and recommended to enhance export earnings. IIUC Studies Vol.16, December 2019: 99-110